2019
DOI: 10.1038/s41598-019-41978-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-regulatory Network of Oncosuppressor miRNAs and Transcription Factors for Pathology of Human Hepatic Cancer Stem Cells (HCSC)

Abstract: Hepatic cancer stem cells (HCSCs) are considered as main players for the hepatocellular carcinoma (HCC) initiation, metastasis, drug resistance and recurrence. There is a growing evidence supporting the down-regulated miRNAs in HCSCs as key suppressors for the stemness traits, but still more details are vague about how these miRNAs modulate the HCC development. To uncover some of these miRNA regulatory aspects in HCSC, we compiled 15 down-regulated miRNA and their validated and predicted up-regulated targets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Additionally, AP-2γ promotes stemness and chemoresistance in the same tumor type although through alterations of different signaling pathway ( 31 ). In contrast, AP-2α is more likely to stimulate MET ( 74 ) and have activity to shift expression profile toward epithelial phenotype suppressing stem cells properties ( 75 ), which might be confirmed by independent experimentally validated AP-2α targets – Insulin-like Growth Factor 1 Receptor ( IGF1R) , Transportin-1 ( TNPO1) and Fatty Acid Synthase ( FASN) – the ones involved in stemness and chemoresistance regulation ( 76 ). Furthermore, endogenous AP-2α expression is thought to be downregulated during EMT induced by TGF-β1 ( 77 ), proving dissimilarity between AP-2α and AP-2γ in terms of the whole TGF-β network which is crucial for EMT ( 78 ).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, AP-2γ promotes stemness and chemoresistance in the same tumor type although through alterations of different signaling pathway ( 31 ). In contrast, AP-2α is more likely to stimulate MET ( 74 ) and have activity to shift expression profile toward epithelial phenotype suppressing stem cells properties ( 75 ), which might be confirmed by independent experimentally validated AP-2α targets – Insulin-like Growth Factor 1 Receptor ( IGF1R) , Transportin-1 ( TNPO1) and Fatty Acid Synthase ( FASN) – the ones involved in stemness and chemoresistance regulation ( 76 ). Furthermore, endogenous AP-2α expression is thought to be downregulated during EMT induced by TGF-β1 ( 77 ), proving dissimilarity between AP-2α and AP-2γ in terms of the whole TGF-β network which is crucial for EMT ( 78 ).…”
Section: Discussionmentioning
confidence: 93%
“…Transcription factors (TFs) are master regulators that regulate gene transcription by binding to the promoter region of the DNA-binding domains of target genes. Moreover, it is known that there is an interplay between host miRNAs and TFs ( Tong et al, 2019 ) during viral infections as shown in Figure 1 , and both are regulated in a coordinated fashion in various biological processes, such as cell proliferation, differentiation, and apoptosis, and many diseases through feed-forward loops (FFLs) and feedback loops (FBLs) ( Tsang et al, 2007 ; Mohamed et al, 2019 ). Therefore, the identification of key regulatory miRNA–TF interactions can play a crucial role in the development of anti-viral therapies against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Canine HCCs exhibit 28 times higher SLC7A5 expression than normal hepatocytes (96). SLC7A5 also plays a critical role in hepatic cancer stem cells (HCSCs) (97). Cellular uptake of glutamine via SLC1A5 and its subsequent efflux in the presence of BCAAs is the rate-limiting step that activates mTORC1 (98).…”
Section: Bcaasmentioning
confidence: 99%